ARTIFICIAL INTELLIGENCE AND HUMAN RESOURCE MANAGEMENT PRACTICES IN DISODEX NIGERIA LIMITED (Journal of the Management Sciences, 2026)
The increasing adoption of Artificial Intelligence (AI) in organizational processes has significantly transformed Human Resource Management (HRM) practices globally. Organizations now leverage AI-driven tools to enhance recruitment efficiency, employee performance management, training, and decision-making accuracy. This study examined the effect of Artificial Intelligence on Human Resource Management practices in Disodex Nigeria Limited. The study adopted a descriptive survey research design. The population of the study comprised employees of Disodex Nigeria Limited, from which a structured questionnaire was administered. Data collected were analyzed using descriptive statistics and regression analysis. Findings revealed that Artificial Intelligence significantly improves recruitment and selection efficiency, employee performance management, and training and development practices. The study concluded that AI-driven HRM practices enhance organizational effectiveness and employee productivity. It was recommended that Disodex Nigeria Limited should invest in AI infrastructure, continuously train HR personnel on AI applications, and ensure ethical deployment of AI systems in HR decision-making.
Keywords: Artificial Intelligence; Human Resource Management; Organizational Effectiveness; Performance Management, Recruitment